Some aspects of effectiveness in Hungarian-Vietnamese business communication - Lenart, Istvan (Scripta Neophilologica Posnaniensia, 2019)
With the aim of revealing linguocultural gaps (lacunas) in Hungarian-Vietnamese business communication, a questionnaire-based study was conducted. A total of 638 questionnaires was completed and analysed. Participants of the survey were Vietnamese individuals who had lived and graduated from university in Hungary, and had a good command of the Hungarian language. In this presentation, the results obtained will be displayed, including linguistic and cultural differences between representatives of the two aforementioned nations. The theoretical background of the study is the Lacuna Theory, developed by the Moscow School of Ethnopsycholinguistics. The results of the survey will hopefully contribute to the further development of the Lacuna Theory in general and in the business context in particular.